Etika Kepemimpinan dalam Era Ai:Tantangan Moral dalam Mengadopsi Ai dalam Organisasi - Nur hasanah; Arul Mu`is; Rizkyna Qur`aini; Mochammad Isa Anshori (Journal Economic Excellence Ibnu Sina, 2025)
This study investigates the role of adaptive leadership in addressing the complex challenges posed by rapid technological advancements, particularly in the era of Society 5.0. The integration of artificial intelligence (AI) into organizational systems introduces not only opportunities for efficiency and innovation but also ethical and leadership dilemmas. Using a literature review methodology, this paper examines how adaptive leadership can support organizations in navigating digital transformation while maintaining ethical integrity and organizational effectiveness. The findings indicate that adaptive leadership—characterized by responsiveness, inclusivity, and value-driven decision-making—is essential for sustaining organizational resilience. Furthermore, the study emphasizes the need for leaders to foster a learning-oriented culture, manage ethical concerns in AI deployment, and apply flexible leadership styles that empower employees. This paper contributes to the growing discourse on ethical digital leadership and offers insights for organizational sustainability in the context of technological disruption.